Seaweed: a sustainable solution for greening drug manufacturing in the pursuit of sustainable healthcare - Leonel Pereira; João Cotas (Exploration of Drug Science)
The environmental impact of drug manufacturing raises concerns about sustainability in healthcare. To address this, exploring alternative approaches to drug production is crucial. This review focuses on seaweed as a sustainable resource for greening drug manufacturing processes. Seaweed offers advantages such as renewability, abundance, and a positive environmental footprint. The review begins by providing an overview of sustainable drug manufacturing practices and the challenges faced in achieving sustainability. It then discusses seaweed as a sustainable resource, including cultivation techniques and environmental benefits. Seaweed has various applications in drug manufacturing, including extracting and purifying bioactive compounds with potential therapeutic properties. Seaweed’s role in developing green technologies, such as seaweed-based excipients, biodegradable packaging materials, and as a source of sustainable energy for drug manufacturing processes, is highlighted. The environmental and economic implications of incorporating seaweed-based solutions are discussed, emphasizing reduced carbon footprint and cost-effectiveness. Regulatory and industrial perspectives are addressed, examining challenges, and opportunities for implementing seaweed-based drug manufacturing. Collaboration between academia, industry, and regulatory bodies is crucial for successful integration. The review presents future directions and opportunities, including emerging trends and innovations in seaweed-based drug manufacturing, areas for further research, policy development, and industry engagement recommendations. Incorporating seaweed into drug production facilitates a reduction in environmental impact, promotes resource efficiency, and contributes to sustainable healthcare. This review showcases seaweed-based solutions as a means to foster a greener future for drug manufacturing, addressing environmental concerns, and promoting sustainability.